Efeito do tratamento com produtos naturais imunomoduladores em camundongos infectados por Schistosoma mansoni - SANTOS, Vitor Augusto Ferreira dos (2024)
Schistosomiasis mansoni is a disease caused by the parasite Schistosoma mansoni. This infection causes millions of deaths annually. Despite advances in science, therapy is still limited, based solely on the use of the drug Praziquantel. Our study aimed to evaluate the effects of the use of natural immunomodulatory products in mice infected with Schistosoma mansoni. We evaluated the hydroalcoholic extract of D. ambrosioides leaves (EHDA) and its combination with Praziquantel, as well as the standardized green propolis extract (EPP-AF®). This work was divided into 2 chapters, Chapter I addresses the anti- Schistosoma effect of D. ambrosioides extract and its combination with PZQ in vivo. The results demonstrate that EHDA and the combination EHDA+PZQ reduced the number of eggs in the feces, liver, intestine, tissue damage in the liver, intestine, and kidney, and reduced the number and area of granulomas in the liver. At 30 and 90 days, both groups reduced blood eosinophilia as well as reduced cellularity of bone marrow, peritoneal lavage, and spleen. In the spleen, the EHDA group reduced CD3+, increased F480+ and LY6G+, and reduced IL-6 and IL-4. The EHDA+PZQ group reduced the number of CD3+, increased the number of CD19+ and F480+, and reduced IL-2, IL-4, and the chemokine MIP-1. Chapter 2 addresses the treatment with EPP-AF® in vitro and in vivo. In vitro, our results show that the concentration of 250 μg/mL reduced the viability of the worms and had a lethal effect at 36 hours. In vivo, the results show that EPP-AF® delayed oviposition and reduced the number of eggs in the feces, liver and intestine. It reduced histopathological damage in the liver, intestine and kidney, in addition to reducing the number and mean diameter of granulomas. At 30 and 90 days, it reduced blood eosinophilia and immunoregulated the cellularity of the bone marrow, peritoneum and spleen. In the spleen, EPP-AF® reduced F480+ and stimulated CD170+, reduced the cytokines IFN-γ, IL-2, IL-6, increased IL-10 and reduced the chemokine MIP-1. This study demonstrates that EHDA and the combination EHDA+PZQ, as well as EPP-AF®, have effective anthelmintic and immunomodulatory activity against the different phases of S. mansoni infection. Delaying oviposition and reducing the parasite load. In addition, the extract modulates the inflammatory profile, reducing histopathological damage and improving the clinical picture of schistosomiasis.